Comprehensive Pharmacogenomic Profiling of Malignant Pleural Mesothelioma Identifies a Subgroup Sensitive to FGFR Inhibition - Quispel-Janssen, Josine M; Badhai, Jitendra; Schunselaar, Laurel; Price, Stacey; Brammeld, Jonathan; Iorio, Francesco; Kolluri, Krishna; Garnett, Matthew; Berns, Anton; Baas, Paul; McDermott, Ultan; Neefjes, Jacques; et al. (Clinical cancer research, 2018)
Despite intense research, treatment options for patients with mesothelioma are limited and offer only modest survival advantage. We screened a large panel of compounds in multiple mesothelioma models and correlated sensitivity with a range of molecular features to detect biomarkers of drug response. We utilized a high-throughput chemical inhibitor screen in a panel of 889 cancer cell lines, including both immortalized and primary early-passage mesothelioma lines, alongside comprehensive molecular characterization using Illumina whole-exome sequencing, copy-number analysis and Affymetrix array whole transcriptome profiling. Subsequent validation was done using functional assays such as siRNA silencing and mesothelioma mouse xenograft models. A subgroup of immortalized and primary MPM lines appeared highly sensitive to FGFR inhibition. None of these lines harbored genomic alterations of FGFR family members, but rather BAP1 protein loss was associated with enhanced sensitivity to FGFR inhibition. This was confirmed in an MPM mouse xenograft model and by BAP1 knockdown and overexpression in cell line models. Gene expression analyses revealed an association between BAP1 loss and increased expression of the receptors FGFR1/3 and ligands FGF9/18. BAP1 loss was associated with activation of MAPK signaling. These associations were confirmed in a cohort of MPM patient samples. A subgroup of mesotheliomas cell lines harbor sensitivity to FGFR inhibition. BAP1 protein loss enriches for this subgroup and could serve as a potential biomarker to select patients for FGFR inhibitor treatment. These data identify a clinically relevant MPM subgroup for consideration of FGFR therapeutics in future clinical studies. .